Pemberdayaan Mayarakat Melalui Kuliah Kerja Nyata (KKN) Reguler Unkriswina Sumba Dibidang UMKM, Pangan Lokal, Pertanian, dan Pendidikan di Desa Mata Lombu - Yuvensius Ramompas; Nersiani Horung; Permus Yengang Peka Pari; Juan Cornelis Missa; Anamaria Erlin Ndima; Imelda Rambu Rija; Ernalinda Ndakularak; Meyfrita Hada Indah Nggandung; Jordan Alethino Nggandung; Diana Saputri Sahoe; Noprianto Hubang; Elroin Landupraing (Lembaga Pengembangan Kinerja Dosen, 2024)
Kuliah Kerja Nyata (KKN) is one of the lecture programs that must be provided and implemented by every university in order to achieve one of the goals and tri dharma, namely Pengabdian Kepada Masyarakat (PKM). Mata Lombu is one of the villages selected to carry out the KKN program, but as a village in Indonesia, it is generally not free from several problems. Based on observations and social analysis carried out, there are various problems that need to be addressed including: (1) lack of community understanding regarding local food processing, (2) lack of understanding of farmers regarding preventing pests in crops, (3) lack of literacy and numeracy among students. Elementary and junior high schools in the village, (5) limited access to clean water, and (6) limitations of MSMEs (Micro, Small and Medium Enterprises) in creating jobs. Based on a number of problems found during observations and social analysis, and the description in the background, the main objective of all these programs is to fulfill community service and empowerment in Mata Lombu Village through a project action planning framework or Project Action Plan (PAP). The series of Unkriswina Sumba Regular KKN activity methods includes the stages of program planning, implementation and evaluation. The results of this activity show that this activity can increase insight, understanding and new knowledge regarding local food, making bokashi fertilizer, making natural pesticides, and tutoring, and can increase crop yields, food security, reduce the impact of environmental pollution, and increase value. increase the economy of village communities.